Вы находитесь на странице: 1из 4

# Math 2443 Homework #3

Solutions
Section 15.4.
Find an equation of the tangent space to the given surface at the specified point.
2. z = 3(x 1)2 + 2(y + 3)2 + 7, (2, 2, 12).
We have z = f (x, y) = 3(x 1)2 + 2(y + 3)2 + 7. Thus,
fx (x, y) =

z
= 6(x 1),
x

fy (x, y) =

z
= 4(y + 3).
y

## An equation of the tangent plane to the given surface at (2, 2, 12) is

z = 12 + fx (2, 2)(x 2) + fy (2, 2)(y + 2)
that is,
z = 12 + 6(x 2) + 4(y + 2).

x2 y 2

6. z = e
, at (1, 1, 1).
2
2
Solution: We have z = f (x, y) = ex y . Thus,
fx (x, y) =

z
2
2
= 2xex y ,
x

fy (x, y) =

z
2
2
= 2yex y .
y

## An equation of the tangent plane to the given surface at (1, 1, 1) is

z = 1 + fx (1, 1)(x 1) + fy (1, 1)(y + 1)
that is,
z = 1 + 2(x 1) + 2(y + 1).
Explain why the function is differentiable at the given point. Then find the linearization
of the function at that point.
12. f (x, y) = x3 y 4 , (1, 1).
Solution: We need to show that the partial derivatives fx and fy are continuous at (1, 1).
We calculate
fx (x, y) = 3x2 y 4 , fy (x, y) = 4x3 y 3
which are clearly continuous at (1, 1), so f is differentiable at (1.1).
The linearization of f at (1, 1) is
L(x, y) = f (1, 1) + fx (1, 1)(x 1) + fy (1, 1)(y 1)
= 1 + 3(x 1) + 4(y 1).
1

Solutions

## Verify the linear

p approximation at (0, 0).
18. f (x, y) = y + cos2 x 1 + 21 y.
Solution: We have
1
fx (x, y) = p
(2 cos x sin x) ,
2 y + cos2 x

1
fy (x, y) = p
.
2 y + cos2 x

## L(x, y) = f (0, 0) + fx (0, 0)x + fy (0, 0)y

1
= 1 + y.
2
Find the differential of the function.
26. v = y cos xy.
Solution: We have
dv =


v
v
dx +
dx = y 2 sin xy dx + (cos xy xy sin xy) dy.
x
y

34. The dimensions of a closed rectangular box are measured as 80 cm, 60 cm and 50
cm, respectively, with a possible error of 0.2 cm in each dimension. Use differentials to
estimate the maximum error in calculating the surface area of the box.
Solution: The surface area of a box of length x, width y and height z is S = 2(xy + yz +
xz). The differential of S is
dS(x, y, z) = Sx (x, y, z)dx+Sy (x, y, z)dy+Sz (x, y, z)dz = 2(y+z)dx+2(x+z)y+2(x+y)z.
Thus, at the point (80, 60, 50), we have
dS(80, 60, 50) = 220dx + 260dy + 280dz.
Since the maximum error in the measurement of each dimension is 0.2, we use dx =
0.2, dy = 0.2 and dz = 0.2. The maximum error in the measurement of the surface area
is
dS = 220(0.2) + 260(0.2) + 280(0.2) = 152 sq cm.
Section 15.5.
dw
Use the Chain Rule
to find dz
dt or dt .
y
1
t
t
4. z = tan
x , x = e ,y = 1 e .

Solution:We have
dz
z dx z dy
=
+
dt
x dt
y dt
!
! 
 y 

1
1
1
t
t
=
e
+
e



2
2
x2
x
1 + xy
1 + xy
!

xet yet
1
=
.
2
x2
1+ y
x

## Use the Chain Rule to find

z
s

and

w
t .

10. z = ex+2y , x = st , y = st .
Solution: We have

Similarly,

z
z x z y
=
+
t
x t
y t
 
 s
 1

.
= ex+2y 2 + 2ex+2y
t
s

z
= ex+2y
s



 

t
1
x+2y
2 .
+ 2e
t
s

Use a tree diagram to write out the Chain Rule for the given case. Assume all functions
are differentiable.
18. R = f (x, y, z, t), where x = x(u, v, w), y = y(u, v, w), z = z(u, v, w), t = t(u, v, w).
Solution This is straight-forward, so I will just produce the answer. Let
Then
fu = fx (xu ) + fy (yu ) + fz (zu ) + ft (tu )
fv = fx (xv ) + fy (yv ) + fz (zv ) + ft (tv )
fw = fx (xw ) + fy (yw ) + fz (zw ) + ft (tw ).
22.
Use the Chain Rule to find the indicated partial derivatives.
u = r2 + s2 , r = y + x cos y, s = x + y sin t;
u u u
x , y , t where x = 1, y = 2, t = 0.
Solution: This directly follows from what we have learned in the class.

R
u

= fu etc.

Solutions

u
2r
2s
=
(cos y) +
(1)
2
2
x
2 r +s
2 r2 + s2
u
2r
2s
=
(1 x sin y) +
(sin t)
2
2
y
2 r +s
2 r2 + s2
2s
u
2r
(0) +
(y cos t).
=
2
2
t
2 r +s
2 r2 + s2
You can substitute the given values of x, y and z to get the answer.
z
z
32. Use Equation 7 to find x
and y
.
xyz = cos(x + y + z).
Solution: Let F (x, y, z) = xyz cos(x + y + z). We compute

Fx (x, y, z) = yz + sin(x + y + z)
Fy (x, y, z) = xz + sin(x + y + z)
Fz (x, y, z) = xy + sin(x + y + z).
By Equation 7, we have
Fx
yz + sin(x + y + z)
z
=
=
x
Fz
xy + sin(x + y + z)
and

Fy
xz + sin(x + y + z)
z
=
=
.
y
Fz
xy + sin(x + y + z)